Evaluation of Laser Effects on the Human Body After Laser Therapy - Khalkhal, Ensieh; Razzaghi, Mohammadreza; Rostami-Nejad, Mohammad; Rezaei-Tavirani, Majid; Heidari Beigvandi, Hazhir; Rezaei Tavirani, Mostafa (Journal of Lasers in Medical Sciences, 2020)
Lasers have wide applications in the treatment and diagnosis of diseases and various medical fields. Laser therapy like the other methods has advantages and disadvantages. Some risks such as bleeding, pain, and infection are created after laser therapy. Explanation and evaluation of laser effects on cell function, tissue, and the body are the aims of this study. We reviewed papers available from 1986 to 2019 about the effects of lasers on cells and tissue. An online search of PubMed, Science Direct and Google scholar using such keywords as “laser”, “cell”, “tissue”, “body” and “side effects” was performed. The laser photons are absorbed by chromophores, resulting in the target heating and localized damage. Laser irradiation alters cellular metabolism and cellular functions. These alterations may be accompanied by undesired side effects which can be monitored via metabolites level change in the body. Based on this finding, laser therapy may be associated with several side effects and complications; therefore, before treatment, the determination of laser types and their properties is necessary to avoid creating side effects. The advantages and disadvantages of the treatment type should be considered in order to choose the best treatment with the least side effects. The patients’ awareness of possible side effects before treatment and also an effective follow-up and management of patients after action are two important points in laser therapy. Training curriculum definition should be determined for laser applicant qualifications in different medical fields.